Assessment of electrocardiographic parameters in healthy dogs undergoing dobutamine stress testing - Sousa, M. G.; Pereira-Neto, G. B.; Carareto, R.; Gerardi, D. G.; Camacho, A. A. (Verlag Hans Huber, 2005)
The electrocardiographic effects of dobutamine stress testing (10 to 40 mu g/kg/minute) were investigated in five conscious healthy dogs. We studied the changes in the duration and amplitude of P wave, PR interval, duration of QRS complex, R wave amplitude, QT interval, and heart rate. Development of arrhythmias and ST segment abnormalities were also recorded. It was observed that dobutamine significantly affects atrioventricular-nodal conduction and total electrical systole time at higher infusion rates. Only a single episode of sustained ventricular tachycardia was observed, which was promptly restored to sinus rhythm shortly after dobutamine infusion was discontinued. No ST segment abnormalities were detected. Dobutamine stress testing was concluded to play a role in some ECG parameters at higher infusion rates.
Keywords: dobutamine stress testing; electrocardiogram; arrhythmia; Catecholamines; Electrophysiology